Mazākumtautību izglītības reforma - Rikmane, Elita (Latvijas Universitāte, 2007)
Maģistra darba tēma ir „ Mazākumtautību izglītības reforma ”. Darba aktualitāte - Izglītības reformas īstenošanas gaita ir sekmējusi sabiedrības vertikālo un horizontālo sašķeltību, ietekmējot arī cittautiešu jauniešu interpretāciju sabiedrībā. Darba mērķis - izpētīt, kā mazākumtautības izglītības reformas kontekstā veidojas skolēnu nostādnes un attieksme pret latviešu valodu, etniskās attiecības un integrācija Latvijas sabiedrībā. Darba gaitā autore secinājusi, ka reformas ietekmē ir uzlabojušās jauniešu latviešu valodas zināšanas, kas pozitīvi ietekmē jauniešu integrāciju Latvijas sabiedrībā.

The theme of Master`s research work is "The educational reform of minorities." The topicality of the research work - Implementation of the educational reform has caused vertical and horizontal splitting of the society having influenced on the interpretation of the young people of other nationalities in the society. The theme of the research work - to explore how the students` attitude to the Latvian language develops in the context with the educational reform of minorities. Attention is paid to ethnic relationships, to the influence of the reform on preserving cultural and national traditions of the minorities and their integration in the Latvian society. In the course of research the author has come to the conclusion, that students` knowledge of the Latvian language has improved, which has a positive influence on their integration in the Latvian society.
Educational reforms of national minorities
Keywords: Vadībzinātne